Supporting Doctoral Students in Crisis - Jennie Golding (Encyclopedia, 2023)
A doctoral student is one undertaking the highest level of university study, leading to a doctoral qualification (of which the traditional and most common form is the PhD), that typically requires they demonstrate a significant contribution to knowledge and their own preparedness to undertake independent research. Crisis in this entry is taken to be a time of great difficulty or a time when a difficult or important decision must be made. In the context of doctoral students, a crisis often brings a threat to the completion of the doctorate.